Ibex-Associated Malignant Catarrhal Fever in Duikers (Cephalophus Spp). Issue 4 (July 2020) - Carvallo, Francisco R.; Uzal, Francisco A.; Moore, Janet D.; Jackson, Kenneth; Nyaoke, Akinyi C.; Naples, Lisa; Davis-Powell, Jordan; Stadler, Cynthia K.; Boren, Brandon A.; Cunha, Cristina; Li, Hong; Pesavento, Patricia A.
Eight duikers, representing 3 different species cohoused in a single zoological collection, died in a 10-month period. Black, red-flanked, and yellow-backed duikers were affected, appearing clinically with a combination of anorexia, diarrhea, ataxia, tremors, and/or stupor, followed by death within 72 hours of onset of clinical signs. Consistent gross findings were pulmonary ecchymoses (8/8), generalized lymphadenomegaly (6/8), ascites (5/8), and pleural effusion (4/8). Dense lymphocyte infiltrates and arteritis affected numerous tissues in most animals. Ibex-associated malignant catarrhal fever (MCF) viral DNA was detected in all cases by polymerase chain reaction and in situ hybridization. Identical ibex-MCF virus sequence was detected in spleen of a clinically healthy ibex ( Capra ibex ) housed in a separate enclosure 35 meters away from the duikers.